An Almost Quadratic Time Algorithm for Sparse Spliced Alignment - Sakai, Yoshifumi (Theory of computing systems, 2011)
The sparse spliced alignment problem consists of finding a chain of zero or more exons from O ( n ) prescribed candidate exons of a DNA sequence of length O ( n ) that is most similar to a known related gene sequence of length n . This study improves the running time of the fastest known algorithm for this problem to date, which executes in O ( n 2.25 ) time, or very recently, in O ( n 2 log 2 n ) time, by proposing an O ( n 2 log n )-time algorithm.